Hypertensive patients’ attended with the family health strategy lifestyle - Paz, Elisabete Pimenta Araujo; Souza, Maria Helena do Nascimento; Mendonça Guimarães, Raphael; Fragoso Pavani, Gabriella; dos Santos Correa, Heloisa Ferreira; de Carvalho, Priscila Moreira; Rodrigues, Ravenna Magalhães (Investigación y Educación en Enfermería, 2011)
Objective. To describe hypertensive patients’ attended with the Family Health strategy lifestyle. Methodology. Cross sectional study, carried out between October 2009 and January 2010. 273 hypertensive patients randomly chosen from the Family Health program attended by three areas of Piraí/RJ (Brazil) participated. For data collection, the “fantastic lifestyle” questionnaire was used. Results. From the studied sample: 61% were women, 56% were 60 and over years of age, 81% had a low level of education and 74% reported having low family income. The most frequent risk factors were: overweight or obesity (72%) and diabetes mellitus (37%). Lifestyle scores were: 13% excellent, 55% very good, 27% good, and 4% poor. Conclusion. Even though lifestyle was considered satisfactory, conditions and health profiles indicate that there are still cardiovascular risk factors.